Borrowing for Growth : Big Pushes and Debt Sustainability in Low-Income Countries - Zanna, Luis-Felipe; Buffie, Edward F.; Portillo, Rafael; Berg, Andrew; Pattillo, Catherine (Published by Oxford University Press on behalf of the World Bank, 2021)
The paper evaluates big push borrowing-and-investment programs in a new model-based framework of debt sustainability that is explicitly designed for policy analysis. The new framework is grounded in a fully-articulated, dynamic macroeconomic model. It allows for financing schemes that mix concessional, external commercial, and domestic debt, while taking into account the impact of public investment on growth and constraints on the speed and magnitude of fiscal adjustment. Supplementing concessional loans with nonconcessional borrowing in world capital markets is generally a high-risk, high-return strategy. It may greatly enhance the prospects for debt sustainability or lead to spectacular failure; much depends on the fine details governing debt contracts, the dynamics of growth, and the speed of fiscal adjustment.